Development and Usability Evaluation of a Nursing Graduate Information Management System (GSMIS) Based on User Experience - Kong, Jingyan (My University, 2022)
[Research Background] Recent years, the rapid development of information technology in colleges and universities and the continuous expansion of graduate students have not only increased the pressure of graduate student management in the School of Nursing of Fudan University, but also accelerated the pace of information technology construction in the college, and the School of Nursing urgently needs to use the existing good platform to realize the information technology of nursing graduate student management in combination with the actual situation of the college, so as to realize the communication between graduate student supervisors, graduate students and management, and also to build an objective and scientific clinical competence assessment system in line with It is also important to provide material for the construction of an objective and scientific clinical competence assessment and evaluation system that is in line with the postgraduate nursing education, which is important to achieve the cultivation goals and improve the quality of nursing graduate training. [Research Purpose] Based on the theory of user experience and the concept of "User-Centered Design", this project develops the information management system for graduate students in the School of Nursing by studying the actual needs of teachers and graduate students in the School of Nursing, which can be divided into the following contents: (1) Construction of the framework content of a Nursing GSMIS (2) Development and testing of a Nursing GSMIS (3) Usability evaluation of the a Nursing GSMIS [Research Methods] 1. Demand analysis of the Nursing GSMIS (1) Preliminary framework: Using target sampling method and maximum variation method, semi- structured interviews were conducted with both faculty and student users of the School of Nursing to build the preliminary framework of the system. (2) Final framework: Expert focus group interviews were used to revise and adjust the required content such as interface design, business functions and performance, and to determine the final framework of the system. 2. Development and testing of Nursing GSMIS The “Rapid Prototype Interaction” model was used to develop the system. After the prototype was developed, the Shanghai Institute of Comprehensive Application of Network Technology was contacted for professional system testing, and then the system was modified and adjusted until it met the research requirements. 3. Usability evaluation of Nursing GSMIS A mixed evaluation method of usability test, questionnaire and qualitative interview was used to conduct a more comprehensive and objective usability evaluation of the GSMIS successfully developed in the early stage. It was used to understand the users' feelings and experiences of the system, analyze the advantages and shortcomings of the system, and explore its actual usability.[Research Results] 1. Demand analysis of Nursing GSMIS (1) Preliminary framework of the system: The faculty and student users interviewed expressed that information management is an important step in the progress of the college and the nursing discipline, and expressed strong support and need for the construction of our information system. Based on the literature review and the needs of faculty and students, the framework was initially formulated as four modules: basic information of admission, cultivation process, research results, and clinical cases. (2)The final framework of Nursing GSMIS: It is built from modules and functions, performance, interface, text, color, etc.; Modules include: basic information module for admission, training process module, scientific research achievement module, clinical case library module, employment information module, graduation tracking module; functions include password setting and retrieval, user log-in, user management, data maintenance, custom query, audit and message notification; Performance can be summarized as follows: data structure is clear, complete, with real-time, expansion, operation and stability; Interface Design is friendly and beautiful, simple and easy to use; Layout should highlight the key points; text design is easy to recognize and read, color design reflects the connotation and characteristics of the college. The performance can be summarized as: clear data structure, complete, real-time, scalability, operability and stability; friendly and beautiful interface design, simple and easy to use, layout to highlight the key points; text design is easy to identify, easy to read, color design reflects the connotation and characteristics of the college. 2. Development and testing of Nursing GSMIS Based on the requirements, the engineers used the “Rapid Prototype Interaction Model” to develop the system. After the prototype was developed, the Shanghai Institute of Comprehensive Application of Network Technology was contacted for professional system testing, and then after many rounds of software discussions and corrections between the software engineers and researchers, the GSMIS finally had the registration and log-in page, the informed consent notification page, the information notification page and six main modules. 3. Usability evaluation of Nursing GSMIS (1) Usability Test: Based on the usability test theory, the target sampling method was used, and five graduate students users were selected to participate in the test is sufficient, and the results are as follows. 1) Quantitative results: The effectiveness was mostly at 100%, and the efficiency was 56.2min/s, 72.2min/s, 53min/s, 225.2min/s, 75.8min/s, 33min/s, and 5.5min/s; The overall score of the post-scene questionnaire (ASQ) was 1.24. The evaluation indexes all indicated that the users rated the system highly. 2) Qualitative results: The test subjects all easily completed and highly praised the system during the test, indicating that the operation was not difficult and satisfied the interaction needs of users. (2) SUS Questionnaire: A total of 40 users completed the SUS using the convenience sampling method and the maximum variance method, and the Mean±SD was 70.23±7.7. Among them, the mean score of the Usability sub-scale was 71.59±8.93 , and the mean score of the ease of Learning sub-scale was 64.77±7.53, with scores ranging from 60 to 70. (3) Qualitative interviews: Using target sampling method and maximum variation method, a total of 10 people were interviewed, including 5 students and 5 staff users, and the number of interviews was 3, with no repeated interviews or secondary interviews. The maximum interview time was 46 minutes, the minimum was 25 minutes, and the average was 35.5 minutes. The results can be summarized into three aspects: general evaluation, content and function evaluation, and shortcomings and improvement. This study combines qualitative and quantitative results, reflecting the good usability of the system, but there are also shortcomings and improvements. [Conclusion] This study used various research methods such as literature review, qualitative interview, and focus group interview to construct a system framework based on user experience, completed the development of the graduate student information management system in the School of Nursing, and used mixed methods such as out-of-sound thinking method, usability testing method, questionnaire survey method, and qualitative interview to evaluate the usability of the system, and the results showed that the system has high acceptance, ease of use, and usability.
Keywords: Graduate student information management system, Usability evaluation, User Experience, Need analysis.